2020
DOI: 10.1016/j.stemcr.2020.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Dishevelled 1-Regulated Superpotent Cancer Stem Cells Mediate Wnt Heterogeneity and Tumor Progression in Hepatocellular Carcinoma

Abstract: Various populations of cancer stem cells (CSCs) have been identified in hepatocellular carcinoma (HCC). Wnt signaling is variably activated in HCC and regulates CSCs and tumorigenesis. We explored cell-to-cell Wnt and stemness heterogeneity in HCC by labeling freshly isolated cancer cells with a Wnt-specific reporter, thereby identifying a small subset (0.4%-8.9%) of Wnt-activity high cells. Further cellular subset analysis identified a refined subset of Wnt-activity high ALDH1 + EpCAM + triple-positive (TP) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…Reilein et al found that the cell types of CSC-derivatives depend in part on the magnitude of spatially graded Wnt pathway activity. 53 The latest report 54 proves the remarkable heterogeneity in Wnt activity in HCC cells, among which Wnt-activity high ALDH1 + EpCAM + triple-positive cells are the most stem-like and highly tumorigenic cells in all CSC populations. This type of cells is called "superpotent CSCs" (spCSC).…”
Section: Wnt Signaling In Cancer Stemnessmentioning
confidence: 99%
“…Reilein et al found that the cell types of CSC-derivatives depend in part on the magnitude of spatially graded Wnt pathway activity. 53 The latest report 54 proves the remarkable heterogeneity in Wnt activity in HCC cells, among which Wnt-activity high ALDH1 + EpCAM + triple-positive cells are the most stem-like and highly tumorigenic cells in all CSC populations. This type of cells is called "superpotent CSCs" (spCSC).…”
Section: Wnt Signaling In Cancer Stemnessmentioning
confidence: 99%
“… 20 Of note, the expression of some CT proteins might be regulated posttranscriptionally; thus, the expression of CT gene mRNA may not guarantee protein expression, which therefore limits its generalization as candidate therapeutic targets. 9 Positive ASPM expression was detected in another HCC cohort, 58 and its prognostic value was also highlighted. The negative ASPM findings in our study might due to the heterogeneous expression pattern of CT genes, or the low sensitivity of the IHC antibody used.…”
Section: Discussionmentioning
confidence: 91%
“…ASPM overexpression has been observed in various cancers ( Xu et al., 2019 , 2020 ; Zhou et al., 2020 ; Alsiary et al., 2014 ; Bruning-Richardson et al., 2011 ; Saleh et al., 2020 ; Xie et al., 2017 ; Tian and Wang, 2020 ; Timaner and Shaked, 2020 ; Hsu et al., 2019 ; Wang et al., 2013 ; Tang et al., 2019 ; Lin et al., 2008 ; Yuan et al., 2020 ; Wu et al., 2021 ) and thus might serve as a prognostic marker in various contexts. ASPM is a positive regulator of the canonical Wnt/β-catenin signaling ( Major et al., 2008 ; Hsu et al., 2019 ) and thus promotes cancer stemness and progression in prostate cancer ( Pai et al., 2019 ) and hepatocellular carcinoma ( Liao et al., 2020 ). Based on this information, and combined with our new data, we posit that ASPM could be a promising therapeutic target in cancers characterized by ASPM-overexpression.…”
Section: Discussionmentioning
confidence: 99%